The Influence of an Australian CEO’s Philosophy and Personality on Shaping Culture - Issa, Theodora; Pick, David (RossiSmith Academic Publishing, 2015)
Leaders are the primary shapers of culture and they need to be far more aware of the importance of culture and how to build it and change it. It will become evident in this case how a CEO’s character influences the culture of his organization and its actions towards community, society, and the environment.